Shared decision-making in healthcare in mainland China: a scoping review - Li, Xuejing; Yang, Dan; Meng, Meiqi; Zhao, Junqiang; Yin, Yiyi; Wang, Hefang; Zhang, Xiaoyan; Liu, Qian; Li, Mengdi; Liu, Jianping; Hao, Yufang (Frontiers in Public Health, 2023)
Background Shared decision-making (SDM) facilitates the participation of healthcare professionals and patients in treatment decisions. We conducted a scoping review to assess SDM’s current status in mainland China, referencing the Ottawa Decision Support Framework (ODSF). Methods Our review encompassed extensive searches across six English and four Chinese databases, and various gray literature until April 30, 2021. Results were synthesized using thematic analysis. Results Out of the 60 included studies, we identified three key themes based on the ODSF framework: decisional needs, decision support, and decisional outcomes. However, there appears to be a lack of comprehensive understanding of concepts related to decisional needs in China. Only a few studies have delved into feasibility, preference, choice, and outcome factors in the SDM process. Another challenge emerges from an absence of uniform standards for developing patient decision aids (PDAs). Furthermore, regarding health outcome indicators, their predominant focus remains on physiological needs. Conclusion SDM is in its infancy in mainland China. It is important to explore the concept and expression of decisional needs in the context of Chinese culture. Subsequent studies should focus on constructing a scientifically rigorous and systematic approach for the development of PDAs, and considering the adaptation of SDM steps to the clinical context in China during SDM implementation. Concurrently, The focus on health outcomes in Chinese SDM studies, driven by the unique healthcare resource landscape, underscores the necessity of prioritizing basic needs within limited resources. Systematic review registration https://inplasy.com/?s=202130021.